2015
DOI: 10.1038/srep11502
|View full text |Cite
|
Sign up to set email alerts
|

Spider wrapping silk fibre architecture arising from its modular soluble protein precursor

Abstract: Spiders store spidroins in their silk glands as high concentration aqueous solutions, spinning these dopes into fibres with outstanding mechanical properties. Aciniform (or wrapping) silk is the toughest spider silk and is devoid of the short amino acid sequence motifs characteristic of the other spidroins. Using solution-state NMR spectroscopy, we demonstrate that the 200 amino acid Argiope trifasciata AcSp1 repeat unit contrasts with previously characterized spidroins, adopting a globular 5-helix bundle flan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
140
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(157 citation statements)
references
References 73 publications
(120 reference statements)
17
140
0
Order By: Relevance
“…During fibre formation, AcSp1 undergoes a partial conversion from α-helical to β-sheet structuring [21], putatively seeded at helix 5 in the W unit [19,22]. This transition is recapitulated in recombinant W 2 between the soluble and fibrous forms [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During fibre formation, AcSp1 undergoes a partial conversion from α-helical to β-sheet structuring [21], putatively seeded at helix 5 in the W unit [19,22]. This transition is recapitulated in recombinant W 2 between the soluble and fibrous forms [19].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous structural studies [19], we performed segmental-labelling using split intein trans -splicing [49,50], whereby either the first (W 2-1 ) or second (W 2-2 ) W unit in W 2 was enriched with NMR-active 13 C and/or 15 N nuclei while the other W unit was at natural abundance. Although we demonstrated differential dynamics between the globular core and linker/tail regions through variation in the observed heteronuclear [ 1 H]- 15 N NOE, a more in-depth analysis of backbone dynamics is necessary to compare and contrast the behaviour of isolated W units vs. concatemers and to provide insight into more subtle variations in dynamics within the W unit.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously expressed recombinant AcSp1-derived constructs with varying numbers of W units (nomenclature: W n , n= number of repeats) in Escherichia coli 36 and demonstrated that W 2 , W 3 , and W 4 constructs can be hand-pulled from low-concentration buffered aqueous solutions to form multi-centimeter fibers 32,36 . However, lowconcentration solutions are inefficient for high-yield fiber production and we have found that increasing W n concentration in aqueous solution promotes non-productive aggregation (results not shown).…”
Section: Introductionmentioning
confidence: 99%
“…AcSp1 undergoes a conceptually similar structural transition, but this results in a highly distinct fibrous structuring. In solution, AcSp1 from A. trifasciata is composed of compactly structured ~138 residue globular helical/turn containing domains connected together by 62 residue intrinsically disordered linkers 32 . Upon fiber formation, the protein retains a similar proportion of disorder and turn content alongside a mixture of moderately oriented β-sheet (~30%) and α-helical (~24%) domains 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…Acriniform silk is also used to form the soft inner layer of egg case. Tremblay et al (2015) found that the high toughness of aciniform silk is related to the primary sequence of spidroin and the distinctive mixture of α-helical, β-sheet, and non-canonical secondary structures. We expect that well understanding of the hierarchical architecture about these silks will inspire to the designs and development of advanced materials.…”
Section: Non-web Spider Silk Materialsmentioning
confidence: 99%